A new perspective on meals as part of an Optimized Mixed Diet for children and adolescents - Kersting, Mathilde; Kalhoff, Hermann; Sinningen, Kathrin; Lücke, Thomas (Frontiers in Nutrition, 2022)
Objectives: To show by the example of the Optimized Mixed Diet (OMD) for children and adolescents in Germany, how the nutrient and food profiles of typical meals in a recommended diet differ and how these typical meal profiles complement each other. Methods: The 7-day menu plan of the OMD with the usual 5 daily meals typical for Germany was used. The total nutrient intake from all meals was compared with the daily reference values. Then meal compositions were optimized. Results: Although the cooked meal (lunch) provides only 25% of the daily energy intake, it is relatively rich (>25% of the daily intake) in most vitamins and minerals, which distinguishes it from the other meals. The cold main meals (breakfast, dinner) are rich in calcium and vitamin B2, due to the preferential use of milk in these meals. The two snacks each provide 12.5% of the daily energy intake. Discussion and Conclusion: The results provide comprehensible guidelines for the composition of all meals of the day for children and adolescents that reflect the existing dietary culture. Differentiated Meal-Based Dietary Guidelines (MBDG) open up the perspective of understanding food as an expression of one's own personality and an invitation to social interaction. Children grow into these specific roles of meals in the family. MBDG could, in a practical way, both facilitate the flexible coordination of family meals and provide guidance for modular meals in day-care centers and schools.